THE DESCRIPTION OF PHYSICAL ACTIVITY AND SEDENTARY BEHAVIOR DURING COVID-19 PANDEMIC ON “X” UNIVERSITY’s STUDENTS - Dian Lesmana; Ignatius Setiawan; Dionisia Vinda Aswada (ODONTO : Dental Journal, 2022)
Background: As of 9th March 2020, World Health Organization declared the outbreak of COVID-19 as a pandemic. The government takes a policy to implement social restrictions aim to restrict COVID-19. The restrictions includes restricted social gatherings, public facilities and closed the schools, so the student can only do learn and their activities from home. This pandemic also affected daily life with physical activity will be impaired and increased sedentary behavior. Method: A descriptive study with cross-sectional design to describe the physical activity and sedentary behavior on university student during the COVID-19 pandemic. Physical activity and sedentary behavior was assessed using Global Physical Activity Questionnaire (GPAQ). The participant of this study were taken using stratified random sampling, and consisted of 297 students drawn proportionally from 9 faculties.Result: The results showed that 129 students (43,4%) included in moderate physical activity category, 92 students (31%) included in low category, and 76 students (25,6%) included in high category. Overall, the average of GPAQ score of 2347 METs per week indicates that students’ physical activity is in moderate category. Male students were more physically active (3448.9METs) than female (1778.6 METs). The study also determine that most of the student had sedentary behavior by sitting or lying down about 327,9 minutes per day.Conclusion: The conclusion is students of different faculties had different physical activity level during this pandemic. Most of the students is in moderate physical activity category and high sedentary behavior.